BO’LAJAK GEOGRAFIYA FANI O’QITUVCHILARINING PEDAGOGIK FAOLIYATINI RIVOJLANTIRISH IMKONIYATLARI VA INNOVATSION YONDASHUVLAR - Bahromova Muhayyo Imomqul qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. The article provides detailed information on opportunities and innovative approaches for developing the pedagogical activities of future geography teachers. It discusses effective teaching mechanisms through modern education, information and communication technologies, and didactic tools, as well as ways to improve quality in higher education institutions. The importance of innovation and novelty in education, their differences, and their impact on the education system are analyzed. The article emphasizes the necessity of using innovative approaches in pedagogical activity to enhance the quality of education and prepare learners as specialists capable of meeting the demands of modern society. The article also analyzes various approaches to implementing pedagogical innovations in higher education institutions, including individual, multi-subjective, humanistic, and individual-creative approaches. It discusses the opportunities for educators to adopt and apply new pedagogical technologies, including the integration of innovative teaching methods and technologies into the classroom process.